Calf muscle strength in former elite distance runners - Trappe, S. W.; Costill, D. L.; Goodpaster, B. H.; Pearson, D. R. (Scandinavian Journal of Medicine & Science in Sports, 1996)
The purpose of this investigation was to examine calf muscle strength and cross-sectional area in 29 middle-aged men (current mean = 48.3 +/- 3.1 years) who had significant differences in their physical activity levels. These men were initially evaluated to determine the physiological requirements for successful distance running in the late 1960s at a time when they were all considered elite distance runners. Based on their training regimens in the interim between testing, subjects were described as highly trained (HI; n = 10), fitness trained (FIT; n = 12), or untrained (UT; n = 7). In addition, an aged-matched sedentary group (CON; n = 7) was tested. Each subject was evaluated for VO2max, plantar flexion calf muscle strength and cross-sectional area (CSA) of the lower leg (gastrocnemius and soleus). Muscle CSA was determined by computed tomography, whereas calf strength measurements were made using a specially designed leg restraint system and an isokinetic dynamometer. There were no significant differences in plantar flexion strength (at 60 and 180 degrees/s) or CSA of the gastrocnemius and soleus muscles among the groups. Calf muscle strength per CSA was also similar at both test velocities for all groups. These data demonstrate that middle-aged distance runners who have continued to run at a relatively high level for 20-25 years have similar calf muscle CSA and strength compared with aged-matched males who run significantly less or not at all.